Peran Stakeholder Dalam Mengukur Rente Ekonomi Perusahaan: Perspektif Baru Terhadap Keunggulan Kompetitif - Grace Yulianti; Mohamad Chaidir; Farah Qalbia (Sekolah Tinggi Ilmu Ekonomi Pariwisata Indonesia Semarang, 2025)
This study aims to explore the role of stakeholders in measuring a company's economic rent and its relationship with competitive advantage. Using a qualitative approach through a literature review, this research analyzes various perspectives and findings on how relationships with stakeholders can influence the creation and utilization of economic rent by companies. The main findings suggest that stakeholders play a crucial role in the value creation process, where effective relationships with both internal and external stakeholders can strengthen a company's competitiveness. This study also highlights the importance of holistic stakeholder management in facing increasingly complex competitive challenges. The findings offer new insights into the role of stakeholders in supporting a company's competitive advantage in a dynamic business environment.